Pruritus Intensity Scales across Europe: a prospective validation study. (3rd February 2021) - Storck, M.; Sandmann, S.; Bruland, P.; Pereira, M.P.; Steinke, S.; Riepe, C.; Soto‐Rey, I.; Garcovich, S.; Augustin, M.; Blome, C.; Bobko, S.; Legat, F.J.; et al.
Abstract: Background: Chronic pruritus (CP) is a subjective symptom, and it is necessary to assess its intensity with validated patient‐reported outcome tools in order to allow determination of the treatment course. Objectives: So far, the itch intensity scales were validated in small cohorts and in single languages. Here, we report the validation of the numerical rating scale, the verbal rating scale and the visual analogue scale for the worst and average pruritus intensity in the last 24h in several languages across Europe and across different pruritic dermatoses. Methods: After professional translation, the intensity scales were digitized for use as a tablet computer application. Validation was performed in clinics for Dermatology in Austria, France, Germany, Italy, Poland, Russia, Spain, Switzerland and Turkey. Results: A total of 547 patients with contact dermatitis, chronic nodular prurigo, psoriasis vulgaris, lichen planus or cutaneous T‐cell lymphoma were included. The intensity scales showed a high level of reproducibility and inter‐correlations with each other. The correlation with the Dermatology Life Quality Index was weak to strong in nearly all countries and dermatoses with the exception of France and patients with chronic nodular prurigo, for which no statistically significant correlations were found. Conclusions: The numerical rating scale, the verbal rating scale und the visual analogue scales are valid instruments with good reproducibility and internal consistency in German (Germany, Austria, Switzerland), French, Italian, Polish, Russian, Spanish and Turkish for different pruritic dermatoses. VAS worst was the best reproducible and consistent measuring instrument in all countries.